The mTOR regulated RNA-binding protein LARP1 requires PABPC1 for guided mRNA interaction. Issue 1 (17th December 2020) - Smith, Ewan M; Benbahouche, Nour El Houda; Morris, Katherine; Wilczynska, Ania; Gillen, Sarah; Schmidt, Tobias; Meijer, Hedda A; Jukes-Jones, Rebekah; Cain, Kelvin; Jones, Carolyn; Stoneley, Mark; Waldron, Joseph A; et al.
Abstract: The mammalian target of rapamycin (mTOR) is a critical regulator of cell growth, integrating multiple signalling cues and pathways. Key among the downstream activities of mTOR is the control of the protein synthesis machinery. This is achieved, in part, via the co-ordinated regulation of mRNAs that contain a terminal oligopyrimidine tract (TOP) at their 5′ends, although the mechanisms by which this occurs downstream of mTOR signalling are still unclear. We used RNA-binding protein (RBP) capture to identify changes in the protein-RNA interaction landscape following mTOR inhibition. Upon mTOR inhibition, the binding of LARP1 to a number of mRNAs, including TOP-containing mRNAs, increased. Importantly, non-TOP-containing mRNAs bound by LARP1 are in a translationally-repressed state, even under control conditions. The mRNA interactome of the LARP1-associated protein PABPC1 was found to have a high degree of overlap with that of LARP1 and our data show that PABPC1 is required for the association of LARP1 with its specific mRNA targets. Finally, we demonstrate that mRNAs, including those encoding proteins critical for cell growth and survival, are translationally repressed when bound by both LARP1 and PABPC1.